1-Benzoyl-5-phenyl-2-(propan-2-yl)-1,2,3,4-tetrahydropyrimidin-4-one - Caracelli, Ignez [UNESP]; Zukerman-Schpector, Julio; Amaral, Monica F. Z. J.; Stefani, Helio A.; Tiekink, Edward R. T. (Wiley-Blackwell, 2009)
The tetrahydropyrimidinone ring in the title compound, C(20)H(20)N(2)O(2), is in a half-boat conformation with the N-C-N C atom 0.580 (2) angstrom out of the plane defined by the remaining five atoms. In the crystal structure, molecules are connected into centrosymmetric dimers via N-H center dot center dot center dot O interactions. The dimeric aggregates are linked into supramolecular chains along the a axis via C-H center dot center dot center dot pi interactions.